Peranan Media Interaktif dalam Mempermudah Guru pada Penyampaian Materi PAI - Muhammad Yusron Maulana El-Yunusi; Dian Farda Al Hasani; Ismail (STAI Ihyaul Ulum Gresik, 2023)
Education plays a very important role in today's life, because education is a medium for improving and developing the quality of every human resource. In line with the rapid development of global education, this requires education to be more abreast of conditions with developments in science and technology. The hope is that the development of science and technology will become an important tool for teachers in achieving educational goals. Educational institutions must be able to utilize technology to maximize the potential of students in competition. Therefore, the authors conducted a survey regarding the role of interactive media in facilitating teachers in delivering PAI material. The method used by the author in this study uses a descriptive qualitative approach. In the process of data analysis, the authors carried out 3 stages, namely data reduction, data presentation and drawing conclusions or proof. Therefore, the findings in this study found that an interactive learning environment is anything, both software and hardware, that can be used as a means to provide learning materials to students by responding to the user's input. mass media. Examples of interactive learning media using interactive CDs, games and software. The importance of interactive media in PAI learning as a means of disseminating material. That the teacher does not only lecture in class, but also as a learning tool to understand the material. PAI is a conscious and periodic effort to prepare students to know, learn, have faith, be pious, have good character, teach the Islamic religion, Al-Quran and Hadith. Interactive media plays an important role in helping teachers to become teaching tools or become learning media..